2021
DOI: 10.15537/smj.2021.42.10.20210293
|View full text |Cite
|
Sign up to set email alerts
|

Impact of body weight on the outcome of pregnancy

Abstract: Objectives: To assess the impact of body weight and body mass index (BMI) on pregnancy outcome. Methods:This prospective cohort study included 3026 pregnant women attending Bakhsh Hospital, Jeddah, Saudi Arabia between July 2017 and June 2019. They were classified according to BMI into normal, overweight, and obese, and were followed up until delivery. The normal group was used as control. Fetal indicators (gestational age at delivery, birth weight, congenital anomalies, Apgar score at 1 and 5 minutes, and adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In this study PPH was more frequent in overweight and obese women (4.0%) compared with normal BMI (2.5%) which is in line with results of Fyfe M E et al [21], Ettedal A and Aljahdal [26] and Humphrey MD [27]. Amal A. El Badawy et al [28] in their study observed that obese women have an increased risk of PPH (OR= 4.01) regardless of mode of delivery.…”
Section: Discussionsupporting
confidence: 90%
“…In this study PPH was more frequent in overweight and obese women (4.0%) compared with normal BMI (2.5%) which is in line with results of Fyfe M E et al [21], Ettedal A and Aljahdal [26] and Humphrey MD [27]. Amal A. El Badawy et al [28] in their study observed that obese women have an increased risk of PPH (OR= 4.01) regardless of mode of delivery.…”
Section: Discussionsupporting
confidence: 90%